2009
DOI: 10.1099/mic.0.025700-0
|View full text |Cite
|
Sign up to set email alerts
|

GFP plasmid-induced defects in Salmonella invasion depend on plasmid architecture, not protein expression

Abstract: We have investigated the impact of plasmids and GFP expression on invasion of cultured epithelial cells by Salmonella enterica Typhimurium strain SL1344. The invasiveness of SL1344 carrying plasmids derived from pBR322, encoding promoterless GFP or constitutively expressed rpsM-GFP, was compared under optimal growth conditions with that of SL1344(pBR322), unmodified SL1344 and a strain with chromosome-integrated rpsM-GFP. The strain carrying pBR322 exhibited normal invasion, but the presence of modified plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…The introduction of AϩT-rich plasmid DNA can thus titrate H-NS away from native chromosomal locations, leading to a mild ⌬hns phenotype with pleiotropic effects, including reduced virulence and motility (3,6). We have shown that H-NS binds strongly in the gfpϩ gene, perhaps explaining a recent report of reduced invasiveness of Salmonella due solely to the presence of a promoterless gfpϩ gene on a multicopy plasmid (2). Over the years, many bacterial studies have relied on plasmid-based gfp fusions, and some of these studies may have experienced unrecognized pleiotropic effects due to H-NS titration.…”
mentioning
confidence: 89%
“…The introduction of AϩT-rich plasmid DNA can thus titrate H-NS away from native chromosomal locations, leading to a mild ⌬hns phenotype with pleiotropic effects, including reduced virulence and motility (3,6). We have shown that H-NS binds strongly in the gfpϩ gene, perhaps explaining a recent report of reduced invasiveness of Salmonella due solely to the presence of a promoterless gfpϩ gene on a multicopy plasmid (2). Over the years, many bacterial studies have relied on plasmid-based gfp fusions, and some of these studies may have experienced unrecognized pleiotropic effects due to H-NS titration.…”
mentioning
confidence: 89%
“…Using microscopy, the number and the distribution or location of bacteria within host cells or cell-associated bacteria can be determined in a proteins from plasmids can affect Salmonella's virulence [28]. Evidence for this was provided by Clark et al [29] who observed a reduction in the expression of Salmonella pathogenic island 1 (SPI-1) genes and a reduced infectivity either in bacteria containing the GFP-expressing plasmid or the empty control plasmid. On the other hand, to avoid the expression of GFP protein from plasmids, the gfp gene can be directly cloned in the bacterial chromosome allowing for its expression from a constitutive promoter [30].…”
Section: Figure 1| Macromolecular Differences Between Cells Of Eukarymentioning
confidence: 99%
“…The SPI-1 T3SS needle structure required for invasion of non-phagocytic cells is encoded by genes located within the prg/org operon (Klein et al, 2000), and expression of prgH, the first gene in the prg/org operon, is regulated by a graded input system that results in an all-or-nothing output (Temme et al, 2008). This can be exploited to produce a reporter system in which expression of GFP driven by the prgH promoter enables the proportion of Salmonella positive for PprgHgfp expression to be used as an index of SPI-1 expression status (Clark et al, 2009;Hautefort et al, 2003;Perrett et al, 2009). Salmonella populations have previously been described as demonstrating heterogeneity of gene expression for prgH, whereby maximal expression (53-70 % positive) occurs in late-exponential phase (Hautefort et al, 2003;Perrett et al, 2009).…”
Section: S Typhimurium Sl1344 Exhibits Increased Susceptibility To Smentioning
confidence: 99%
“…Following infection, cells were washed thoroughly in PBS and fixed in 2 % (w/v) PFA overnight. Differential adhered/invaded staining and quantification were carried out as previously described (Clark et al, 2009;Perrett & Jepson, 2007).…”
mentioning
confidence: 99%